Penentuan Hasil Ujian Karateka Inkanas Menggunakan Metode WSM Berbasis WEB - Muhammad Hozi Prayuda; Syafri Arlis; Harkamsyah Andrianof (CV. ITTC INDONESIA, 2025)
The INKANAS Karate School of West Sumatra routinely conducts promotion tests for its karateka. However, the assessment process is still carried out manually, which risks subjectivity and inefficiency. This research aims to design a Decision Support System (DSS) based on the Weighted Sum Model (WSM) method to determine promotion eligibility more objectively and systematically. The system uses three criteria: Kihon, Kata, and Kumite, and was developed using PHP and MySQL. This DSS is expected to support a more transparent and efficient decision-making process.